Penerapan Metode Simple Additive Weighting dalam Penentuan Prioritas Program Pembangunan Daerah - Siagian, Jaya Sari Anggraini; Purba, Bister; Ambarsari, Erlin Windia; Rohayani, Hetty (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Regional governments and institutions related to preparing regional development programs experience several obstacles in determining regional development work plans, one of which is difficulty in determining development priorities that are in line with regional regulations. The effectiveness and efficiency of implementing regional development programs depends on the accuracy of the data collected. One of the challenges faced by the Medan City Regional Development Planning Agency is the lack of consideration of the priority scale and fairness in the regional development stages, as well as the absence of a system that can help determine the priority scale. Therefore, this research requires a decision support system (DSS). In the SPK, there are many solution methods that can be used according to the needs of each problem. In this research, to determine regional development program priorities, the SAW method will be used. Of the 10 proposed regional programs, only one will be a priority development program. After applying the SAW method in making decisions, the development program that has the highest priority level is the highway construction program with the final result obtained, namely 0.77705.